Impact of deceased-donor characteristics on early graft function: outcome of kidney donor pairs accepted for transplantation - Mahler, Christoph F.; Friedl, Felix; Nusshag, Christian; Speer, Claudius; Benning, Louise; Göth, Daniel; Schaier, Matthias; Sommerer, Claudia; Mieth, Markus; Mehrabi, Arianeb; Renders, Lutz; Heemann, Uwe; et al. (Frontiers in Immunology, 2024)
Introduction The impact of deceased donor characteristics on kidney transplant outcomes is controversial. Correspondingly, the predictive performance of deceased donor scores remains moderate, and many transplant centers lack validated criteria for graft acceptance decisions. To better dissect donor-related risk from recipient and periprocedural variables, we analyzed outcomes of kidney donor pairs transplanted in different individuals. Methods This study explored (a)symmetry of early outcomes of 328 cadaveric kidney transplant recipients from 164 donor pairs transplanted at three Eurotransplant centers. The primary discriminatory factor was (a)symmetry of partner graft function, defined as early graft loss or impaired graft function [estimated glomerular filtration rate (eGFR) <30 mL/min] 3 months after transplantation. We reasoned that a relevant impact of donor factors would result in a high concordance rate of limited graft function or failure. Results The observed number of symmetric graft failure after transplantation was less than statistically expected (3 months: 1 versus 2, p = 0.89; and 12 months: 3 versus 5, p = 0.26). However, we found a trend toward an impaired 5-year graft survival of grafts with good function 3 months after transplantation but a failed or impaired partner graft compared to symmetrically well-functioning grafts (p = 0.09). Subsequently, we explored the impact of individual donor and recipient variables on early transplant outcomes. Generalized estimating equations after feature selection with LassoGEE bootstrap selected donor age, donor body mass index, and donor eGFR as the relevant risk factors. Discussion Our findings indicate that donor factors impact early outcomes in kidney transplantation but may have a limited role in long-term graft survival, once a graft has been accepted for transplantation. Utilizing donor-based clinical scores has the potential to aid clinicians in acceptance decisions, giving them an estimate of individual posttransplant outcomes. However, the ultimate decision for acceptance should rest with clinicians, who must consider the complex interplay of donor factors, as well as recipient and periprocedural characteristics.